Efficacy and safety of Wuling San for treatment of breast-cancer-related upper extremity lymphoedema: study protocol for a pilot trial. Issue 12 (16th December 2016) - Zhu, Huiru; Peng, Zheng; Dai, Meiyu; Zou, Yan; Qin, Fengxian; Chen, Jifei; Song, Liuying; He, Baoyu; Lv, Xiaolan; Dai, Shengming
Abstract : Introduction: Breast-cancer-related upper extremity lymphoedema (BCUL), a common complication of mastectomy, can cause physical discomfort, psychological distress, cosmetic defects, functional disability and chronic recurrent erysipelas in the affected arm(s). It is a challenge to physicians involved in the management of these patients. Wuling San, a classic prescription in Traditional Chinese Medicine used in treating oedema for thousands of years, is reported by many Chinese journals to perform well in BCUL. Therefore, the aim of this study is to verify its efficacy and evaluate its safety using rigorous methodological designs in patients with BCUL. Methods and analysis: To verify the efficacy and assess the safety of Wuling San over a placebo, this double-blind, randomised, placebo-controlled, multicentre trial will be carried out in three hospitals. A total of 200 eligible patients with BCUL will be randomly allocated, in a ratio of 1:1, to either the experimental medicine group or the placebo group. The primary outcome measure will be the proportion of absolute reduced limb volume, as measured by perometry. The second outcome measure will be the number of participants with adverse events. The assessment will be carried out at the following time points: before enrolment (baseline) and 2, 4, 6 and 8 weeks after treatment. Ethics and dissemination: This trial will be conducted in accordance with the Declaration of Helsinki and supervised by the institutional review board of the Fourth Affiliated Hospital of Guangxi Medical University (approval number PJK2016088). All patients will receive information about the trial in verbal and written forms and will give informed consent before enrolment. This trial will help to demonstrate whether Wuling San is effective in the treatment of patients with BCUL. The results will be published in peer-reviewed journals or disseminated through conference presentations. Trial registration number: NCT02726477 ; Pre-results.